Aging and dying: medical and ethical considerations - Drane, James F. (Acta Bioethica, 2001)
The idea of writing a chapter on aging seems particularly appropriate. I'm at the right age to address this topic. As I did the preparatory reading and research, I had an unusual experience. For the first time in my life, I felt like an expert. I could judge what people were saying about aging by my own experience. Besides facing aging myself, I work mainly with rural hospitals and nursing homes and hospice organizations where most of the patients are elderly. Both in my personal life and in my work, I am surrounded by the realities of aging and dying. In a recent book entitled Gray Dawn (1) on the economics and politics of aging, the author, Peter Peterson used a gripping metaphor to describe the challenge of an increasing aging population. Global aging, he said, is like a massive iceberg which very well could destroy even the most powerful economic vessels in the world. The aging population worldwide, according to this author, threatens human survival and is the most important challenge we face in the 21st century. His iceberg metaphor highlights the danger of global aging and the fact the all human beings are exposed to this danger.